Thirteen days in September Carter, Begin, and Sadat at Camp David - Wright, Lawrence 1947- (New York Alfred A. Knopf, 2014)
With his hallmark insight into the forces at play in the Middle East and his acclaimed journalistic skill, Lawrence Wright takes us through each of the thirteen days of the Camp David conference, delving deeply into the issues and enmities between the two nations, explaining the relevant background to the conflict and to all the major participants at the conference, from the three heads of state to their mostly well-known seconds working furiously behind the scenes
Includes bibliographical references and index
1
Keywords: Begin, Menachem -- 1913-1992; Carter, Jimmy -- 1924-; Sadat, Anwar -- 1918-1981; Camp David Agreements -- (1978); Israel-Arab War, 1973 -- Peace; United States -- Foreign relations -- 1977-1981